IMPLEMENTATION OF DISCOVERY LEARNING USING WEBBED AND SHARED TYPES IN IMPROVING STUDENT LEARNING OUTCOMES - Fitria, Yanti; Agasi, Diren; Prakarsa Arzfi, Bima (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study aims to determine how effective the learning process in elementary schools using discovery learning models using learning with webbed and shared types on 3rd grade 4th theme to improve student learning outcomes. This research method uses a quasi-experimental method, where the sample data used are not selected at pure randomness, but are selected by random class. In this research apply The Matching – only Pretest-Postest Control Group Design. This research was conducted at one of SDN which is located in Kapur IX District, Lima Puluh Kota Regency. The results showed that the disco very learning learning model accompanied by the webbed and shared integration types was able to improve student learning outcomes, so that in practice the two types of integration did not experience significant differences, as evidenced by the results of the t-test which showed the two types of integration did not show any significant difference. significant difference when applied in the learning process in two different class groups.